Development of Electronic Network as a Media Strengthening Autonomy of Sekaran Village, Loceret District, Nganjuk Regency in Order to Fulfill the Mandate of Law - Fauzan Aliwarman; Rohmatul Faizah (Nusantara Science and Technology Proceedings)
Rural development today has experienced significant changes in the concept and process. The concept of development is no longer limited to the agricultural sector and basic infrastructure but it leads to the development of Information and Communication Technology (Electronic Networks). The process of rural development then increasingly reduced dependence on government roles. This activity was specifically aimed at village officials of Sekaran Village, Loceret District, Nganjuk Regency to be a mobilizer and motivator that was based on electronic network for young people and the wider community in general for the benefit of villages and reduce the negative impact of technology by making corrective and preventive measures. The method used was through mentoring and training in managing websites and social media and community empowerment. The results of this activity showed an increase in knowledge, understanding, and raising awareness of young people and villagers towards the benefits of technology and the internet for the advancement of Sekaran Village.